2018
DOI: 10.1161/atvb.38.suppl_1.105
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 105: Increased Circulating Trimethylamine N-oxide (TMAO) Augments the Incidence of Abdominal Aortic Aneurysm in Low Penetrant C57BL/6J Mice

Abstract: Background: The gut microbiota is a metabolically active endocrine organ critical to the maintenance of cardiovascular health. Dietary sources of choline are metabolized by microbial enzymes to form trimethylamine (TMA). Metabolism by the host hepatic enzyme flavin-containing monooxygenase 3 (FMO3) converts TMA to the pro-inflammatory molecule trimethylamine N-oxide (TMAO). Human clinical trials have correlated high levels of circulating TMAO to an increased risk of cardiometabolic diseases. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The cardiac system is a major site where these metabolites can give rise to severe health consequences by inducing cardiovascular diseases (CVDs) ( 30 32 ). TMAO has been realized to enhance plaque accumulation inside the arteries (atherosclerosis) ( 33 ), platelet reactivity and blood coagulation (thrombosis) potential ( 34 , 35 ), blockage of arteries in coronary artery disease ( 36 ), the risk of heart failure, vascular inflammation ( 37 , 38 ), as well as abdominal aortic aneurysm ( 39 ) ( Figure 1 ). Some studies have shown that elevated levels of TMAO could also increase the accumulation of macrophage cholesterol and upregulate several macrophage scavenger receptors associated with atherosclerosis ( 40 ) [for more information on gut phage-bacteria interplay and the interactions of bacterial metabolites in cardiometabolic diseases, see ( 41 )].…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac system is a major site where these metabolites can give rise to severe health consequences by inducing cardiovascular diseases (CVDs) ( 30 32 ). TMAO has been realized to enhance plaque accumulation inside the arteries (atherosclerosis) ( 33 ), platelet reactivity and blood coagulation (thrombosis) potential ( 34 , 35 ), blockage of arteries in coronary artery disease ( 36 ), the risk of heart failure, vascular inflammation ( 37 , 38 ), as well as abdominal aortic aneurysm ( 39 ) ( Figure 1 ). Some studies have shown that elevated levels of TMAO could also increase the accumulation of macrophage cholesterol and upregulate several macrophage scavenger receptors associated with atherosclerosis ( 40 ) [for more information on gut phage-bacteria interplay and the interactions of bacterial metabolites in cardiometabolic diseases, see ( 41 )].…”
Section: Introductionmentioning
confidence: 99%